Recent developments in enzyme immobilization technology for high-throughput processing in food industries - Taheri-Kafrani, Asghar; Kharazmi, Sara; Nasrollahzadeh, Mahmoud; Soozanipour, Asieh; Ejeian, Fatemeh; Etedali, Parisa; Mansouri-Tehrani, Hajar-Alsadat; Razmjou, Amir; Yek, Samaneh Mahmoudi-Gom; Varma, Rajender S (Critical reviews in food science and nutriton, 2021)
The demand for food and beverage markets has increased as a result of population increase and in view of health awareness. The quality of products from food processing industry has to be improved economically by incorporating greener methodologies that enhances the safety and shelf life via the enzymes application while maintaining the essential nutritional qualities. The utilization of enzymes is rendered more favorable in industrial practices via the modification of their characteristics as attested by studies on enzyme immobilization pertaining to different stages of food and beverage processing; these studies have enhanced the catalytic activity, stability of enzymes and lowered the overall cost. However, the harsh conditions of industrial processes continue to increase the propensity of enzyme destabilization thus shortening their industrial lifespan namely enzyme leaching, recoverability, uncontrollable orientation and the lack of a general procedure. Innovative studies have strived to provide new tools and materials for the development of systems offering new possibilities for industrial applications of enzymes. Herein, an effort has been made to present up-to-date developments on enzyme immobilization and current challenges in the food and beverage industries in terms of enhancing the enzyme stability.
Keywords: technologie; Food Industry; Enzymes, Immobilized; Enzyme Stability; potravinářský průmysl; enzymy imobilizované; stabilita enzymů; Technology